Sharia Accounting Perspective: The Influence of Community Participation, Use of Information Technology, and Apparatus Competence on Village Fund Management Accountability - Nila Ayu Kusuma Wardani; Nur Hikmah; Sofia Ulfah; Mar'atus Sholikah; Purwati Purwati (ITB AAS INDONESIA Surakarta, 2023)
The aim of this research is to find out whether community participation, use of information technology, and apparatus competence have a positive effect on the accountability of village fund management and to examine the accountability of village fund management from a Sharia Accounting perspective. This research is a quantitative research where the population in this study was obtained from 15 villages with 75 respondents. The sampling technique used was purposive sampling. Data was obtained by documentation and questionnaires using multiple linear regression analysis. The results of this research show that Community Participation, Use of Information Technology and Apparatus Competence each have a positive and significant effect on village fund management accountability. Accountability from an Islamic economic perspective will be realized if village officials are able to fulfill their obligations to convey their mandate and responsibility for what they have done to agencies or communities who have the right to accept that accountability.